The Influence of C3A Content in Cement on the Chloride Transport - Min Jae Kim; Ki Beom Kim; Ki Yong Ann (Advances in Materials Science and Engineering)
The present study concerns the influence of C3A in cement on chloride transport in reinforced concrete. Three modified cement was manufactured in the variation of the C3A content, ranging from 6.0 and 10.5 up to 16.9%. The setting time of fresh concrete was measured immediately after mixing, together with the temperature at the time of initial set. For properties of hardened concrete in the variation in the C3A, a development of the compressive strength and chloride permeation were measured using mortar specimens. Simultaneously, chloride binding capacity was measured by the water extraction method. To ensure the influence of pore structure on chloride transport, the pore structure was examined by the mercury intrusion porosimetry. As a result, it was found that an increase in the C3A content resulted in an increase in chloride binding capacity. However, it seemed that increased binding of chlorides is related to the higher ingress of chlorides, despite denser pore structure. It may be attributed to the higher surface chloride, which could increase the gradient of chloride concentration from the surface, thereby leading to the higher level of chloride profiles. Substantially, the benefit of high C3A in resisting corrosion, arising from removal of free chlorides in the pore solution, would be offset by increased chloride ingress at a given duration, when it comes to the corrosion-free service life.